2019
DOI: 10.1186/s43159-019-0005-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Maximum Surgical Order Schedule (MSBOS) among pediatric patients to optimize blood utilization

Abstract: Background: Evaluating blood ordering and subsequent development of a blood ordering schedule can decrease over-ordering of blood among pediatric surgical patients. The objective is to assess our practice of blood utilization using various blood utilization indices and calculate the Maximal Surgical Blood Order Schedule (MSBOS). This is a cross-sectional study for 3 years that included patients (≤ 18 years old) who underwent major surgical procedures in the Philippine Children's Medical Center. Data included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The average of the actual transfused RBC units per surgery, i.e., the transfusion index, is one of the most commonly adopted factors [13][14][15][16][17], which is used widely in blood banks in South Korea [2][3][4][5][6][7][8][9]. Many studies recommended and adopted the type and screen for cases with TI<0.5 [16,18,19]. This study used the criterion TI≥0.5 to seek relevant changes in MSBOS.…”
Section: Discussionmentioning
confidence: 99%
“…The average of the actual transfused RBC units per surgery, i.e., the transfusion index, is one of the most commonly adopted factors [13][14][15][16][17], which is used widely in blood banks in South Korea [2][3][4][5][6][7][8][9]. Many studies recommended and adopted the type and screen for cases with TI<0.5 [16,18,19]. This study used the criterion TI≥0.5 to seek relevant changes in MSBOS.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a significant portion of blood utilization is attributed to elective surgeries, 17 which is somewhat unexpected given that transfusion requirements are higher in non‐ESP compared to ESP 18,19 . Despite the implementation of a maximal surgical blood order schedule to improve the efficiency of blood ordering practices for ESP, 20 crossmatch‐to‐transfusion ratios remain high and/or blood is underutilized 21,22 . Respondents were not asked to identify surgeries that were impacted explicitly.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that for the given period in this post-neonatal ward the average transfusion probability was 100%. Accordingly, a value of 30% and above has been suggested to be appropriate and signies the appropriateness of number of 5,8,20 units' cross matched.…”
Section: Discussionmentioning
confidence: 99%